Synthesized Silver Nanoparticle Loaded Gel of Curcuma Caesia for Effective Treatment of Acne - Rai, Nivedita; Shukla, Tarkeshwar P.; Loksh, Kavita R.; Karole, Sarita (Journal of Drug Delivery and Therapeutics, 2020)
Objective: The objective of our research is to prepare silver nanoparticles from the rhizome extract of Curcuma caesia and develop topical herbal gel formulation for the effective treatment of acne. Methods: In this present study, silver nanoparticles were synthesized using hydroalcoholic extract of Curcuma caesia rhizome. Silver nanoparticles loaded gels were evaluated for pH, viscosity, spreadability, in vitro release, estimation of total flavonoids and alkaloid content and antibacterial (propioni bacterium acne) studies. Results: The synthesized silver nanoparticles were stable, spherical shape with average particle size of 220.5 nm. The results obtained in the developed formulation showed no lumps, had uniform color dispersion and were free from any fiber and particle. It was also observed to have easy washablity, good spreadability, pH was found to be 6.58±0.02 and 7.02±0.01 similar to pH of the skin. The antibacterial study of the developed formulation showed inhibitory activity against Propioni bacterium acne. Synthesized silver nanoparticle loaded gel displayed drug release of optimized formulation F3 follows the Higuchi kinetic model, and the mechanism is found to be non Fickian/anomalous according to Korsmeyer–Peppas. Silver nanoparticles effectively inhibited the growth of both microorganism indicating good antibacterial properties. Conclusion: Synthesis of silver nanoparticles using Curcuma caesia is a new, green method and not reported yet, as per literature survey done for this project. Successful synthesis and evaluation of silver nanoparticles was proved by the in-vitro study. Keywords: Curcuma caesia, Silver nanoparticles, Propioni bacterium acne, Acne, Flavonoids content, Alkaloid content, Antibacterial.